2005
DOI: 10.1124/jpet.105.086413
|View full text |Cite
|
Sign up to set email alerts
|

Despite Similar Anxiolytic Potential, the 5-Hydroxytryptamine 2C Receptor Antagonist SB-242084 [6-Chloro-5-methyl-1-[2-(2-methylpyrid-3-yloxy)-pyrid-5-yl Carbamoyl] Indoline] and Chlordiazepoxide Produced Differential Effects on Electroencephalogram Power Spectra

Abstract: Serious efforts have been made to develop anxiolytics with improved clinical utility and reduced side effects. 5-Hydroxytryptamine (5-HT) 2C receptor antagonists are potential anxiolytics; however, their effects on vigilance are not well characterized. To compare the effects of benzodiazepines and subtype-selective 5-HT 2C receptor antagonists on anxiety, vigilance, and electroencephalogram (EEG) power density, social interaction test and polygraphic recordings were performed in male Sprague-Dawley rats after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
5
13
1
Order By: Relevance
“…Similarly, 5-HT 2C antagonists consistently enhance active social interaction in rats, and S32006 was likewise effective in this procedure (Kennett et al 1996b(Kennett et al , 1997Wood et al 2001;Martin et al 2002;Kantor et al 2005;Harada et al 2006;Millan et al 2005). The "ceiling" effect in the social interaction procedure was not unexpected inasmuch as 5-HT 2C antagonists-and other anxiolytics-generally display biphasic dose-response curves in this model File and Seth 2003).…”
Section: Modulation Of Frontocortical Monoaminergic Transmissionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, 5-HT 2C antagonists consistently enhance active social interaction in rats, and S32006 was likewise effective in this procedure (Kennett et al 1996b(Kennett et al , 1997Wood et al 2001;Martin et al 2002;Kantor et al 2005;Harada et al 2006;Millan et al 2005). The "ceiling" effect in the social interaction procedure was not unexpected inasmuch as 5-HT 2C antagonists-and other anxiolytics-generally display biphasic dose-response curves in this model File and Seth 2003).…”
Section: Modulation Of Frontocortical Monoaminergic Transmissionmentioning
confidence: 67%
“…Inasmuch as activation of 5-HT 2B receptors in the amygdala enhances social interaction, their blockade is unlikely to participate in the anxiolytic properties of S32006 (Kennett et al 1996a;Millan 2003). Nonetheless, 5-HT 2B receptors modulate sleep-wake cycle architecture (Smith et al 2002;Kantor et al 2004Kantor et al , 2005Cespuglio et al 2005;Millan 2006), so a possible role of their blockade in the influence of S32006 upon sleep (Descamps-Lefebvre et al 2008) should not be discounted.…”
Section: Modulation Of Frontocortical Monoaminergic Transmissionmentioning
confidence: 99%
“…The polygraphic recordings were classified by sleep analysis software for the 24-h recordings (SleepSign for Animal, Kissei Comtec America Inc.). EEG power spectra were computed for consecutive 4-s epochs at the frequency range of 0.25-30 Hz (fast Fourier transformation routine, Hanning window ; frequency resolution, 0.25 Hz) (Kantor et al, 2002(Kantor et al, , 2005.…”
Section: Sleep Recording and Scoringmentioning
confidence: 99%
“…For example, in preclinical rodent studies, 5-HT 2C R-selective antagonists have demonstrated antidepressant-like effects (Dekeyne et al, 2008), enhanced the antidepressant-like effects of selective serotonin reuptake inhibitors (Cremers et al, 2004), and displayed an anxiolytic-like spectrum of behaviors (Kantor et al, 2005;Harada et al, 2006;Burghardt et al, 2007;Dekeyne et al, 2008). Although the precise neurobiological mechanism of action underlying these effects remains unclear, studies have consistently demonstrated that 5-HT 2C Rs exert a modulatory role on dopamine (DA) activity.…”
Section: Introductionmentioning
confidence: 99%